The relationship between corporate social responsibility and work engagement: The mediating role of affective commitment and the moderating role of responsible leadership - Duarte, A. P.; Simões, L. M. (HRM conference 2024 : 13th Biennial International Conference of the Dutch HRM Network, Abstracts, 2024)
Sustainable development goals (SDGs) impose added challenges to organizations. As key agents of such development pattern, organizations must integrate social and environmental considerations, along economic ones, in their daily activities and business strategies. While getting companies onboard is essential for the success of the 2030 agenda, the path forward is not always clear. Introducing corporate social responsibility (CSR) practices within the organization, companies can foster work engagement. This involves the voluntary adoption by organizations of practices encompassing environmental, social, and stakeholder concerns, which has emerged as a key instrument in their strategy to achieve success and gain an advantage in an increasingly competitive market (European Commission, 2001; Duarte & Neves, 2011). By having these types of practices on the organization, companies will be able to foster work engagement.